2015
DOI: 10.9738/intsurg-d-14-00193.1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Transversus Abdominis Plane Block and Rectus Sheath Block in Laparoscopic Inguinal Hernia Surgery

Abstract: We aimed to assess the efficacy of transversus abdominis plane (TAP) block and rectus sheath (RS) block in patients undergoing laparoscopic inguinal hernia surgery. Few studies have addressed the efficacy and safety associated with TAP block and RS block for laparoscopic surgery. Thirty-two patients underwent laparoscopic inguinal hernia surgery, either with TAP and RS block (Block þ group, n ¼ 18) or without peripheral nerve block (Block À group, n ¼ 14). Preoperatively, TAP and RS block were performed throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Intrathecal anaesthesia with morphine provides good pain control but causes itching in half of the women and nausea or vomiting in one in five . The rectus sheath block can reduce opioid requirements after transverse laparotomy in children , elective caesarean sections without intrathecal morphine , major gynaecological surgery , laparoscopic inguinal hernia repair , laparoscopic cholecystectomy and gynaecological cancer surgery with midline incision . Multimodal analgesia may reduce the rate of chronic pain after caesarean sections .…”
Section: Introductionmentioning
confidence: 99%
“…Intrathecal anaesthesia with morphine provides good pain control but causes itching in half of the women and nausea or vomiting in one in five . The rectus sheath block can reduce opioid requirements after transverse laparotomy in children , elective caesarean sections without intrathecal morphine , major gynaecological surgery , laparoscopic inguinal hernia repair , laparoscopic cholecystectomy and gynaecological cancer surgery with midline incision . Multimodal analgesia may reduce the rate of chronic pain after caesarean sections .…”
Section: Introductionmentioning
confidence: 99%
“…RSB can be used for analgesia in cases of umbilical, paraumbilical and epigastric hernia surgery [9], for somatic analgesia in laparotomy surgery when epidural anesthesia is contraindicated [10] and for midline trocar sites analgesia in laparoscopic surgery [11]. There are published data about RSB use for paraumbilical analgesia in patients with cardiovascular compromise, when neuraxial anesthesia was risky or contraindicated [9].…”
Section: Original and Clinical Articlesmentioning
confidence: 99%
“…Compared to placebo or local wound infiltration analgesia, the rectus sheath block results in lower pain scores with opioid-sparing effects in both children and adults receiving umbilical hernia repair [56,57,59]. Study reports have also demonstrated that this block provides effective pain control in surgeries involving midline incisions [60,61].…”
Section: Evidence and Clinical Applicationsmentioning
confidence: 99%
“…Study reports have also demonstrated that this block provides effective pain control in surgeries involving midline incisions [60,61]. The rectus sheath block can be used in combination with the TAP block for pain relief over a wider area in surgeries involving the anterior abdominal wall [57,62]. Potential complications following the rectus sheath block include peritoneal or bowel perforation, hematoma, and local systemic toxicity.…”
Section: Evidence and Clinical Applicationsmentioning
confidence: 99%